The Impact of Intensive Utilization of Cultivated Land on Grain Yields: A Case Study of Shandong Province in China - Wang, Ruozhou; Jiang, Yanqing (International Journal of Sustainable Agricultural Research, 2018)
Using time series data of agriculture in Shandong Province during the period from 2000 to 2015, this paper sets up an assessment system of intensive utilization of cultivated land, which has 4 criteria(input intensity, utilization intensity, output effectiveness and sustainability) consisting of 9 indices, comprehensively estimates the level of intensive use of agricultural land with entropy method, and empirically analyzes the impact of intensive utilization of cultivated land on grain yields through the use of a multivariable linear regression model. The results are shown as follows: (1) The level of intensive utilization of cultivated land in Shandong Province has been fluctuating upwards but not significantly progressing. (2) Grain yield per hectare is positively correlated with output effectiveness and utilization intensity, and the contribution of output effectiveness to grain yield per hectare is more than the other. (3) grain yield per hectare is negatively correlated with input intensity and sustainability. Therefore, in the long-term, cultivated land management strategy should be planned to improve the input intensity, to emphasis on the sustainability of farm land and to promote the consciousness of cultivated land protection in order to increase the productivity of grain yields.